Standardization of media and container for improving seed and seedling growth in papaya (Carica papaya) cv. Red Lady - PANT, POOJA; VERMA, M K (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted to standardize the suitable media and type of the container for improving seed germination and seedling growth of papaya (Carica papaya L.) cv. Red Lady during 2019–20. Five different types of media and three types of containers were used for study. Present experiment was conducted in a Complete Randomized Block Design (Factorial) with 15 treatment combinations replicated thrice. The observations were recorded on seed germination attributes and seedling growth parameters. The results showed that the plastic containers were found better followed by earthen pots and polybags using media mixture of soil + cocopeat + vermicompost (1:1:1) for improving seed germination (94.76%). However, the maximum plant height (17.40 cm), number of leaves (12.03), stem girth (6.42 mm), leaf area (131.02 cm2), root length (18.60 cm) and seedling survival (97.30%) was observed in the earthen pots having rooting media mixture made up of garden soil + cocopeat + vermicompost + FYM (1:1:1:1). The seed germination and plant growth parameters, root length and seedling survival was recorded in polybags.